Evaluation of clinical data in patients that underwent different surgical treatments for spontaneous pneumothorax - Jakupi N.; Yankov G.; Stevic M.; Jovanovski-Srceva M. (World Wide Journals, 2021)
Introduction: Spontaneous pneumothorax (SPT) is surgically treated with two different techniques: Video Assisted Thoracoscopy (VATS) or open thoracotomy (OT). Despite the different invasiveness of the techniques, literature gives controversial results in correlation of the techniques to the clinical outcomes (like length of hospital stay (LOHS), recurrences of the pneumothorax, duration, collection of the drains and etc). The aim of our study was to analyze perioperative clinical features in patients that underwent SPT treatment surgically. Materialsandmethods: prospectively,weevaluateddataofpatientstreatedforSPTintwo-yearperiodattheUniversityclinicforthoracic surgery in Skopje. Patients were divided into VATS group and OT group, according to the surgical technique used for treatment. In both groups we analyzed demographical, laboratory data, duration of the chest drains presence, early inammatory markers and total LOHS. Patients with recurrent pneumothorax, older than 70 years with severe cardiological impairment were excluded. Results: The study included 42 patients, 23 patients (54.8%) underwent VATS treatment and 19 patients (45.2%) underwent OT. In both groups more patients were male. VATS group of patients showed nonsignicant difference in postoperative laboratory and inammatory ndings, non- signicantly lower presence of the drains in terms of days, signicantly lower drain uid collections for the rst 3 days and signicantly shorter LOHS compared to the OT group. Conclusion: Our study has showed that patients treated for spontaneous pneumothorax with VATS have shorter length of hospital stay, shorter chest drain presence and overall show better outcome.
Keywords: VATS; spontaneous pneumothorax; open thoracotomy; LOHS